2010
DOI: 10.1111/j.1539-6924.2010.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

A Social‐Cognitive Model of Pandemic Influenza H1N1 Risk Perception and Recommended Behaviors in Italy

Abstract: The outbreak of the pandemic influenza H1N1 2009 (swine flu) between March and April 2009 challenged the health services around the world. Indeed, misconceptions and worries have led the public to refuse to comply with precautionary measures. Moreover, there have been limited efforts to develop models incorporating cognitive, social-contextual, and affective factors as predictors of compliance with recommended behaviors. The aim of this study was to apply a social-cognitive model of risk perception and individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
200
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(211 citation statements)
references
References 41 publications
7
200
2
2
Order By: Relevance
“…Existing research on the public's response to pandemic influenza emphasises compliance with PARs and assesses measures for dealing with the problem of noncompliance with warnings (Casman and Fischhoff, ; Wein and Atkinson, ; Balkhy et al, ; Prati, Pietrantoni, and Zani, ). A few studies have looked at how and why people adopt PARs in the context of a pandemic.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Existing research on the public's response to pandemic influenza emphasises compliance with PARs and assesses measures for dealing with the problem of noncompliance with warnings (Casman and Fischhoff, ; Wein and Atkinson, ; Balkhy et al, ; Prati, Pietrantoni, and Zani, ). A few studies have looked at how and why people adopt PARs in the context of a pandemic.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…However, few studies have tested these hypotheses within any theoretical frameworks. Studies of pandemic influenza A/H1N1 found that older respondents perceived greater severity of, but lower personal susceptibility to the disease while males generally perceived lower severity of and personal susceptibility to the disease [15, 17]. Few studies reported the relationships between educational attainment and risk perception of influenza.…”
Section: Introductionmentioning
confidence: 99%
“…In October 2009 (four months after the start of the Level 6 alert) we modified a previously implemented survey and conducted a second national Canadian survey on pandemic preparedness and management ethics [9] which remained in the field until May 2010 during considerable fluctuations in risk perceptions, influenced by personal experiences and media reports on during the outbreak [10,11]. Survey responses were likely influenced by these socio-environmental fluctuations [12]. …”
Section: Introductionmentioning
confidence: 99%